International Treaties (Mu’âhadât) in Islam: Theory and Practice in Light of Islamic International Law (Siyar) according to Orthodox Schools By Labeeb Ahmed Bsoul (Lanham, MD: University Press of America, 2008. 216 pages.) (American Journal of Islam and Society, 2010)
In the post-9/11 era and with increasing tension between the Islamic and thenon-Islamic worlds due to al-Qa’ida’s purported global jihad, Labeeb Bsoul’sstudy of the Islamic law of international treaties is certainly a timely contributionto an important topic. While this work represents a fairly comprehensiveresource for researchers in this area insofar as it gathers the opinions ofnumerous pre-modern (and some modern) scholars of Islamic law on variousissues related to war and peace between Islamic and non-Muslim states,it is, unfortunately, no more than a simple compilation of their views.Indeed, the author provides no meaningful historical framework by which one could trace doctrinal development or tie these doctrines to a wider historicalor philosophical tradition of international law. Those looking foranswers regarding the possibilities for mutual co-existence between Muslimand non-Muslim states on the basis of mutual equality will be severelydisappointed ...